2003
DOI: 10.1021/jp026535r
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Hydration of Cyanamide and Carbodiimide

Abstract: The isomerization reaction cyanamide f carbodiimide in vacuo and in the presence of up to six water molecules has been investigated by means of DFT and MP2 calculations, using a flexible basis set. The reliability of such methods has been checked against results of coupled cluster calculations on isolated molecules. The effect of water molecules has also been investigated in the case of the hydrolysis reaction of cyanamide and carbodiimide, leading to isourea. The number of water molecules considered is large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 67 publications
10
57
0
Order By: Relevance
“…These can be considered as conservative estimates, which also account for the approximations made and for neglecting higher-order correlation effects. From Tables 1, 2, 3, 4 and 5, it is evident that all isomers considered have been previously studied at different levels of theory [11,[41][42][43][44][45][46][47][48], but we report the first systematic investigation of their molecular structure. As in most cases the method and/or the basis set used are inferior to ours, a detailed comparison of these results to ours is not too meaningful.…”
Section: Molecular Structurementioning
confidence: 99%
“…These can be considered as conservative estimates, which also account for the approximations made and for neglecting higher-order correlation effects. From Tables 1, 2, 3, 4 and 5, it is evident that all isomers considered have been previously studied at different levels of theory [11,[41][42][43][44][45][46][47][48], but we report the first systematic investigation of their molecular structure. As in most cases the method and/or the basis set used are inferior to ours, a detailed comparison of these results to ours is not too meaningful.…”
Section: Molecular Structurementioning
confidence: 99%
“…We found that an amidine with a 74-like structure does not correspond to a minimum and, instead, rotation about the C2-N3 bond via transitionstate structure 74 results in amino-group transfer along the down path from 74 to 75. tautomer of carbodiimides 9 and 9= and of cyanoimines 10 and 10=. In the gas phase, the activation barrier for the isomerization between the prototypical carbodiimide and cyanamide is over 330 kJ/mol [53]. The tautomerization of 95 to 10= requires an activation enthalpy of ⌬H act H Ï­ 162.71 kJ/mol but even this low barrier apparently does not allow for competition with decarbonylation and 1,2-Hshift to 96 (m/z 107).…”
Section: Esi-ms Of Guanosinementioning
confidence: 99%
“…A possible reason is that hydrolysis side reaction of cyanamide occurred during the guanidinylation reaction. 25 …”
Section: Characterization Of Guanidinylated Chitosanmentioning
confidence: 99%